Successful Surgical Management of Dystocia in a Cat - Parmar, KH; Vadaliya, JV; Kaval, RJ; Vala, KB; Chikhaliya, PS (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
In the polytocus small animals there may be a complete or a partial failure of the uterus to start contracting. In partial failure the uterus may bring the first fetus to the pelvic inlet from where it is delivered by abdominal straining. No further fetuses were present and uterine contraction ceases. An idiopathic type of primary uterine inertia has been described, in which delivery starts normally and several members of the litter are delivered normally. There is no evidence of obstruction to birth through maternal or fetal cause. The uterus stops contracting and does not resume unless ecbolic therapy is given. It could be argued that this could be classified as a partial rather than a complete primary uterine inertia (Peter Jackson, 2004).Uterine inertia that is lack of normal physiologic uterine contraction during or after parturition, is a common condition encountered in bovine. However, it is comparatively less reported in canine and feline.